Teaching Strategies of Public Senior High School Teachers in Improving the Lifelong Learning Competencies of Students in the New Normal - Manzano, Emed Ferrer (Jurnal Pendidikan Progresif, 2023)
Teaching Strategies of Public Senior High School Teachers in Improving the Lifelong Learning Competencies of Students in the New Normal[e1] . Objective: The goal of this study is to characterize the teaching strategies, methods of instruction and strategies in encouraging responsibilities for learning in the new normal. Methods: The study used a descriptive method of research to assess the extent of teaching strategies to enhance students’ lifelong learning competencies. The respondents were the teachers in public senior high schools in the province of Ilocos Sur, Philippines.  A questionnaire was used to collect pertinent data and it was analyzed using frequency count, percentage and mean. Finding: The results revealed that teaching strategies used by teachers in the new normal is characterized by giving complex activities, practicing social negotiation introducing multiple perspectives giving activities to exercise ownership of learning valuing self-awareness in knowledge construction which is assumed to develop lifelong learning practices. Conclusion: Teachers hone lifelong learning competencies through engaging active learning, giving feedbacks, designing meaningful interactions, and respecting diverse ideas.  Keywords: teaching strategies, new normal, lifelong learning, competencies, descriptive study.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202342